2022
DOI: 10.1002/aic.18006
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ni‐Al layered double hydroxide via coprecipitation: Formation mechanism, synthesis intensification, and catalytic application

Abstract: Herein, the formation mechanism of Ni-Al layered double hydroxide (NiAl-LDH) synthesized by coprecipitation was explored. Moreover, NiAl-LDH was prepared in a rotating packed bed (RPB) under different rotation speeds, which shows that increasing the rotation speed decreases the lateral size and thickness of NiAl-LDH, since high rotation speed accelerates the nucleation of NiAl-LDH. Additionally, the Ni/mixed metal oxides (MMO) catalysts derived from NiAl-LDH were prepared for maleic anhydride (MA) hydrogenatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 82 publications
(124 reference statements)
0
1
0
Order By: Relevance
“…24 Process intensification has been considered to be one of the most promising progress paths for developing more sustainable chemical processes. 25,26 High-gravity technology based on rotating packed bed (RPB) is typical process intensification technology with great potential for industrial applications due to its high mass-transfer efficiency, which has been applied in the preparation of nanoparticles, 27,28 polymers, 29,30 and emulsions. 31,32 It has also been preliminary demonstrated that a variety of rare-earth doped nanophosphors with more uniform doping can be obtained by introducing high-gravity at the premixing stage, such as Zn 2 GeO 4 :Mn 2+ nanophosphors, 33 CaMoO 4 :Yb 3+ /Er 3+ phosphors, 34 and NaYF 4 : Gd 3+ /Yb 3+ /Er 3+ nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…24 Process intensification has been considered to be one of the most promising progress paths for developing more sustainable chemical processes. 25,26 High-gravity technology based on rotating packed bed (RPB) is typical process intensification technology with great potential for industrial applications due to its high mass-transfer efficiency, which has been applied in the preparation of nanoparticles, 27,28 polymers, 29,30 and emulsions. 31,32 It has also been preliminary demonstrated that a variety of rare-earth doped nanophosphors with more uniform doping can be obtained by introducing high-gravity at the premixing stage, such as Zn 2 GeO 4 :Mn 2+ nanophosphors, 33 CaMoO 4 :Yb 3+ /Er 3+ phosphors, 34 and NaYF 4 : Gd 3+ /Yb 3+ /Er 3+ nanoparticles.…”
Section: Introductionmentioning
confidence: 99%